Atracurium and intraocular pressure. Issue 9 (September 1985) - Murphy, D F; Eustace, P; Unwin, A; Magner, J B
Abstract : The effect of atracurium on intraocular pressure was studied by comparing it with pancuronium in a randomised controlled trial. The intraocular pressure was measured in patients undergoing cataract surgery before administration of the muscle relaxant, at 1, 3, and 5 minutes after its administration, and at 1 minute after tracheal intubation. Atracurium was found to decrease intraocular pressure to a significantly greater degree than pancuronium. The intraocular pressure after tracheal intubation was found to be significantly higher than that measured immediately after induction of anaesthesia. The authors conclude that atracurium provides an acceptable alternative to pancuronium for ophthalmic surgery but does not overcome the ocular hypertensive effect of tracheal intubation.